CRISPR/Cas12a Coupled With Recombinase Polymerase Amplification for Sensitive and Specific Detection of Aphelenchoides besseyi - Zhang, Anpeng; Sun, Bin; Zhang, Jianming; Cheng, Can; Zhou, Jihua; Niu, Fuan; Luo, Zhongyong; Yu, Luzhen; Yu, Cui; Dai, Yuting; Xie, Kaizhen; Hu, Qiyan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Aphelenchoides besseyi (A. besseyi), a seed-borne parasitic nematode, is the causal agent of rice white tip disease (RWTD), which may result in drastic loss of rice yield. Seed treatments are currently considered to be the most effective means of RWTD prevention and spread. Therefore, the rapid, highly specific and accurate detection of A. besseyi from rice seed is crucial for the surveillance, prevention and control of RWTD. Here, we describe a novel detection assay that combines recombinase polymerase amplification (RPA) and CRISPR/Cas12a to detect A. besseyi (termed RPA-Cas12a-Ab), with a low limit-of-detection (LOD) of 1 copy/μl of plasmid or 1:107 diluted DNA extracted from individual nematode. To improve the user-friendliness, lateral flow strip (LFS) technique was adopted to visualize the detection result. The LOD of RPA-Cas12a-Ab LFS assay was 1000 copies/μl plasmid or 1:10 diluted DNA extracted from individual nematode. The assay developed in this study was able to identify A. besseyi in 45 minutes with high accuracy sensitivity without cross-reaction with three closely related non- A. besseyi species. Thus, RPA-Cas12a-Ab is a rapid, sensitive, and specific detection system that requires no sophisticated equipment and shows promise for on-site surveillance of A. besseyi.